2005
DOI: 10.1016/j.bios.2004.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the binding properties of a synthetic anion receptor using rational and combinatorial strategies

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…In chloroform, investigation of anion affinity of 12a is complicated by the fact that the peptide adopts a non-symmetrical conformation stabilized by an intramolecular hydrogen bond. 78 Since affinity of neutral receptors that rely on hydrogen bonding for anion coordination generally decrease with increasing polarity of the solvent 79 it was particularly surprising when we detected strong interactions of 12a with anions such as sulfate and halides in highly competitive protic solvent mixtures such as 80% D 2 O-CD 3 OD. 77 The reason for this unusual behavior turned out to be the special structure of the complexes formed.…”
Section: Anion Coordination To Amide Groupsmentioning
confidence: 97%
See 2 more Smart Citations
“…In chloroform, investigation of anion affinity of 12a is complicated by the fact that the peptide adopts a non-symmetrical conformation stabilized by an intramolecular hydrogen bond. 78 Since affinity of neutral receptors that rely on hydrogen bonding for anion coordination generally decrease with increasing polarity of the solvent 79 it was particularly surprising when we detected strong interactions of 12a with anions such as sulfate and halides in highly competitive protic solvent mixtures such as 80% D 2 O-CD 3 OD. 77 The reason for this unusual behavior turned out to be the special structure of the complexes formed.…”
Section: Anion Coordination To Amide Groupsmentioning
confidence: 97%
“…85 Comparison of the binding equilibria on the basis of the association constants determined for 12a and 13a showed that anion complexation of the bis(cyclopeptide) is significantly more efficient than that of the monotopic analog. 78 A systematic evaluation of the influence of linker structure on anion affinity has also been performed. For this, the sulfate and halide affinities of bis(cyclopeptides) 13b-c (Chart 7), whose linkers become progressively more rigid, were compared to that of 13a.…”
Section: Anion Coordination To Amide Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Artificial biomimetic receptors containing amide and urea groups as anion recognition sites constitute one of the largest sub-groups in this field (Asthana et al, 2013;Chang et al, 2015;Ge et al, 2014;Kubik et al, 2005;Lin et al, 2015;Pinter et al, 2013;Warwick et al, 2013;White and Beer, 2013;White et al, 2014, Warwick et al, 2013. Chloride recognition with these systems is mostly achieved by hydrogen bonding interactions, which in many cases are not strong enough to overcome the high energy of hydration (ΔG = -340 kJ/mol) besides the fact that water molecules efficiently compete for the binding sites (Butler and Parker, 2013;Kubik, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, examples of the combination of noncovalent interactions and dynamic covalent bonds have also appeared 3bg. DCC has received increasing attention because new catalysts, receptors, and sensors have been identified by using this approach 2fj…”
Section: Introductionmentioning
confidence: 99%